Epidemic Rumination and Resilience on College Students' Depressive Symptoms During the COVID-19 Pandemic: The Mediating Role of Fatigue - Ye, Baojuan; Zhou, Xiuxiu; Im, Hohjin; Liu, Mingfan; Wang, Xin Qiang; Yang, Qiang (Frontiers in Public Health, 2020)
During the pandemic of COVID-19, the blockade control of all sectors of society and the uncertainty of the development of the epidemic have bring a certain degree of adverse psychological state to college students isolated at home. Although ruminations have been shown to play an important role in depression, little is known about mediating and moderating mechanisms underlying this relationship. In the present study, we examined the mediating role of fatigue in the association between epidemic rumination and depression and the moderating role of resilience. 1293 Chinese college students completed the measures of epidemic ruminations, fatigue, depression, and resilience. The results indicated that epidemic ruminations were significantly and positively associated with depression, and fatigue partially mediated this relationship. Moderated mediation analysis further indicated that resilience moderated the relationship between epidemic ruminations and fatigue. The relationship became weaker for college students with higher levels of resilience. Results highlight the significance of identifying the mechanisms that moderate the mediated paths between epidemic rumination and depression, which have important implications for the prevention and intervention of depression among college students.